Strategi Kebijakan Impor Garam Dalam Melindungi Produksi Garam Nasional - Ghozali, Adein Bagus Maulana; Samputra, Palupi Lindiasari (HK-Publishing, 2022)
AbstractThis study aims to analyze the salt import policy strategy in protecting national salt production. The method used in this research is research synthesis, in the form of a literature review of previous research results from 2011 to 2020 with the same topic. The study results are contradictory to the impact of the salt import policy on national salt production. Negative impact: decreasing farmers' welfare and the price of people's salt, causing salt farmers to have difficulty producing capital for national salt. Positive implications: becoming a price control for domestic prices, encouraging the quality of the people's salt to compete with imported salt. The salt import policy strategy to protect national salt production is as follows: (1) There must be improvements to the Regulation of the Minister of Trade of the Republic of Indonesia Number 63 of 2019 concerning Salt Imports' Provisions. For example, setting HPP for people's salt as outlined in a ministerial regulation. (2) To accommodate the Indonesian People's Salt Farmers Association's aspirations in policymaking, (3) Support from the government for technology in producing people's salt, (4) The government can set price control during the salt harvest season.Keywords: Strategy, Salt Import Policy, National Salt Production.Â AbstrakPenelitian ini bertujuan untuk menganalisis strategi kebijakan impor garam dalam melindungi produksi garam nasional. Metode yang digunakan dalam penelitian ini adalah sintesis riset, berupa literature review terhadap hasil-hasil penelitian terdahulu dari tahun 2011 hingga 2020 dengan topik yang sama. Hasil penelitian terdapat kontradiksi dari dampak kebijakan impor garam terhadap produksi garam nasional. Dampak negatif: Â Â menurunnya kesejahteraan petani dan harga garam rakyat, sehingga menyebabkan petani garam kesulitan modal untuk memproduksi garam nasional. Dampak positif: menjadi price control terhadap harga dalam negeri, mendorong kualitas garam rakyat sehingga dapat bersaing dengan garam impor. Strategi kebijakan impor garam untuk melindungi produksi garam nasional sebagai berikut: (1) Harus adanya penyempurnaan peraturan Menteri Perdagangan Republik Indonesia Nomor 63 Tahun 2019 Tentang Ketentuan Impor Garam. Seperti, menetapkan HPP garam rakyat yang dituangkan dalam peraturan menteri. (2) Menampung aspirasi Asosiasi Petani Garam Rakyat Indonesia dalam pembuatan kebijakan, (3) Dukungan dari pemerintah terhadap teknologi dalam memproduksi garam rakyat, (4) Pemerintah bisa menetapkan price control pada masa panen raya garam.Kata Kunci: Strategi, Kebijakan Impor Garam, Produksi Garam Nasional.